Premixed early strength type flow state solidified soil and preparation method thereof
The premixed early-strength fluidized solidified soil composition addresses the balance between fluidity and early strength by using slow-absorbing microspheres and slow-release particles, ensuring high fluidity and rapid strength development, suitable for municipal and highway construction.
Patent Information
- Application Number
- CN202411254910.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Existing technologies face challenges in achieving a balanced unity between early strengthening and premixing of fluidized solidified soil, particularly in the context of municipal and highway construction, where fluidity loss during transportation and insufficient early strength hinder the application of fluidized solidified soil in narrow spaces.
A premixed early-strength fluidized solidified soil composition comprising 85-96 parts of mud, 4-15 parts of curing agent, 0.008-0.05 parts of retarder, 0.0048-0.03 parts of slow-absorbing water microspheres, and 0.012-0.06 parts of slow-release early-strength particles, where the microspheres and particles are coated with specific acrylic resins to control fluidity and enhance strength development.
The solution ensures high fluidity during transportation and rapid strength development post-application, with fluidity maintained above 200 mm for 2 hours and 24h strength reaching 0.2-0.6 MPa, meeting municipal and road engineering requirements for early strength and premixing.
Smart Images

Figure BDA0005033731530000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of mud solidification, and in particular to a premixed early-strength fluidized solidified soil and a preparation method thereof. Background Art
[0002] With the rapid development of infrastructure construction, a large amount of engineering waste mud is generated during the construction of shield tunnels, bored piles, underground continuous walls, etc. In addition, with the continuous deepening of water environment governance, a large number of rivers and lakes have begun to be dredged and desilted, resulting in a large amount of dredged mud. Both engineering mud and dredged mud have the characteristics of high water content and low strength. Direct stacking or discharge will occupy a large amount of land and cause environmental pollution. At present, dredged mud and engineering waste mud are mostly dehydrated by geomembrane bags or plate and frame filter press technology, and landfill treatment is carried out after dehydration, occupying a large amount of land resources. In addition, flocculants need to be added during the dehydration process of mud, which is not only costly but also the removed water needs to be treated to meet the standards before it can be discharged, and the process is cumbersome. Therefore, exploring ways to recycle dredged mud and engineering waste mud has always been a concern in the engineering and environmental protection fields.
[0003] In addition, in the process of new construction and renovation and expansion of municipal roads and highways, it is often necessary to build corresponding hydraulic, electric and other pipelines. After the pipeline is laid, the surrounding voids need to be backfilled, and the backfill area needs to be rolled multiple times to achieve a certain degree of compaction to prevent the backfill area from settling and affecting the road surface structure. However, due to the small space in this part of the backfill area, large and medium-sized compaction machinery cannot be used, and it can only be compacted by manual tamping, resulting in insufficient density of the backfill soil and the quality of the project cannot be guaranteed. For this reason, graded crushed stone and plain concrete are often used in the project to backfill the small space around the pipeline to ensure the quality of the project. However, both plain concrete and graded crushed stone have the problem of high prices, and a large amount of cement and / or crushed stone are required when preparing the above two materials, which have problems such as high energy consumption and environmental pollution.
[0004] Fluidized solidified soil is an ideal material for backfilling in narrow spaces. This technology is to add a curing agent to mud with a certain fluidity, stir it evenly and then pour it. It is necessary to ensure that it has high fluidity during pouring and that it can form a certain strength after pouring. Preparing dredged mud and engineering waste mud into fluidized solidified soil for backfilling in narrow spaces can not only solve the problem of mud landfill occupying a large amount of land, but also replace raw materials such as plain concrete and graded crushed stone, with outstanding environmental and economic benefits. At present, fluidized solidified soil is mainly used for backfilling in narrow areas such as foundation pit fertilizer troughs and platform backs. These areas have no requirements for the early strength of fluidized solidified soil, and the requirements for its 28d strength are not high, usually 0.2~1.0MPa.
[0005] However, when fluidized solidified soil is used for backfilling of pipe corridors of municipal roads and highways, there are two core technical problems that need to be overcome. The first is the early strengthening of fluidized solidified soil. The construction and expansion projects of municipal roads and highways (especially the expansion and expansion of urban roads) are often under tight construction schedules. After the pouring of fluidized solidified soil, it is necessary to quickly form strength (to meet the requirements of construction machinery walking after 24 hours) to ensure the continuous construction of subsequent superstructures (such as ash soil layer, water-stable layer, surface layer, etc.) to ensure the progress of the project. The second is the premixing of fluidized solidified soil. The construction and expansion projects of municipal roads and highways often do not have the site for preparing fluidized solidified soil on site, but need to be premixed in the factory; however, fluidized solidified soil requires high fluidity. When premixing in the factory is used, the technical problem of fluidity loss during transportation needs to be solved to expand the transportation radius and ensure the continuous supply of large-scale fluidized solidified soil. However, the existing technical means cannot solve the above two core technical problems at the same time. The main reason is that there is a certain contradiction between the early strengthening and premixing of fluidized solidified soil. Because the existing fluidized solidified soil premixing technology mainly improves fluidity by using water reducing agent or increasing the initial water content of mud, and at the same time, adding some retarder to delay the loss of fluidity of premixed fluidized solidified soil during transportation, but the increase in initial water content and the effect of retarder will reduce the early strength of fluidized solidified soil, making it difficult for fluidized solidified soil to achieve early strength. Therefore, how to effectively achieve the balance between early strengthening and premixing of fluidized solidified soil is a practical problem and technical difficulty faced by the application of fluidized solidified soil in the backfill of narrow spaces in new construction and renovation and expansion projects such as municipal roads and highways.
[0006] Patent CN107459301A discloses a premixed fluidized solidified soil. This method uses soil, water, a curing agent, and a foaming agent to prepare the fluidized solidified soil. Under the conditions of 16% to 44% curing agent and 12% to 30% foaming agent, the 28d strength can reach 1.78 to 6.98 MPa. However, the early strength of the fluidized solidified soil is not analyzed, and the attenuation of fluidity (slump) over time is not evaluated, so true premixing is not achieved.
[0007] Patent CN111908855B discloses a composite pile premixed fluidized solidified soil slurry and its preparation method. The fluidized solidified soil prepared by the method using clay, cement, fine sand, water, fly ash, carboxymethyl cellulose, ethylene glycol monoallyl ether, triethanol, sodium sulfate, calcium sulfoaluminate, etc. has high strength, and the crack resistance and segregation resistance of the fluidized solidified soil are greatly improved, but the technical solution does not solve the technical problem of early strengthening of the fluidized solidified soil.
[0008] Patent CN115108751B discloses a dispersant for premixed fluidized solidified soil, and its preparation method and application. This technology adjusts the strength of fluidized solidified soil at different ages by the water-reducing effect of the anti-viscosity water-reducing agent under the premise of improving the fluidity of the silty clay slurry, and realizes the rapid dispersion of the silty clay slurry, providing key technical support for the construction process of preparing premixed fluidized solidified soil from original soil under non-drying conditions. However, in the embodiment, the 14d unconfined compressive strength is only about 0.5MPa, and the early strengthening of the fluidized solidified soil is not achieved.
[0009] Patent CN117003529A discloses a method for preparing self-compacting premixed fluidized solidified soil using mud, cement, desulfurized ash, carbide slag, fly ash, soil penetrant, high-performance water reducer and polyester fiber. However, the 7d strength of the fluidized solidified soil prepared by this technology is only about 0.2MPa, which cannot meet the requirements of early strength. In addition, the fluidity of the fluidized solidified soil in this technical solution is 160-180mm, and there is no retarding technical measure, which makes it difficult to meet the requirements of high fluidity and premixing of the fluidized solidified soil.
[0010] Patent CN110723938B discloses a fluidized solidified soil and its preparation method. This technology uses slag, pottery sand, water, cement, fly ash, and early strength agent to prepare fluidized solidified soil with certain early strength function. In the embodiment published by this technology, the initial fluidity is 180-250mm, the 1d unconfined compressive strength is 0.05-0.1MPa, and the 7d unconfined compressive strength is 0.3-0.4MPa, which meets certain early strength function, but this technology does not have any retarding technical measures and cannot meet the requirements of premixing.
[0011] Patent CN114477926B discloses a fluid solidified soil based on waste mud and slag from slurry shield and its preparation method. In this technology, fast-hardening sulphoaluminate cement is used to achieve early strength, and a 7d unconfined compressive strength of 0.2-0.33MPa is achieved under the conditions of 10-20% fast-hardening sulphoaluminate cement, 10-15% fly ash, 4-8% steel slag and 4-8% blast furnace slag. However, this technology does not evaluate the 24h strength of fluid solidified soil, nor does it achieve premixing.
[0012] Patent CN116143468A discloses a premixed fluidized solidified saline soil and a preparation method thereof. The method uses saline soil, iron tailings sand, cement, slag, steel slag, fly ash, magnesium salt, activator, water reducer and water to prepare premixed fluidized solidified soil. The method achieves the control of the fluidity of the fluidized solidified soil to above 160 mm within 3 hours after mixing, which can meet the requirements of pumping and realize the premixing function, but the method does not evaluate its 24h strength. Patent CN115975650A discloses a flow aid for preparing high-fluidity solidified loess, a preparation method and a use thereof, although it realizes a partial premixing function, it also fails to achieve early strengthening.
[0013] Patent CN115784701B discloses a self-curing fluidized solidified soil composite curing agent and its application. The method uses cement, slag, gypsum, carbide slag, microbial curing agent, and self-curing microbeads to prepare a composite curing agent and a fluidized solidified soil. The data published in the examples of the patent show that a 3d strength of 0.5 to 0.65 MPa can be achieved under the condition of an initial fluidity of 190 to 205 mm, and it has good shrinkage resistance. However, the patent does not realize the premixing of fluidized solidified soil.
[0014] Patent CN116332611B discloses a premixed fluidized solidified soil and its preparation method. The method uses soil, water, ordinary cement, sulphoaluminate cement, aluminate cement, early strength polycarboxylate water reducer, slow release polycarboxylate water reducer, anti-mud polycarboxylate water reducer, melamine water reducer, concrete strong nucleus, retarder, early strength agent, shrinkage reducer, viscosity regulator to prepare fluidized solidified soil. Although the method achieves an initial fluidity of 220-230mm, a 1h fluidity of 205-215mm, and a 6h strength of 0.7-2.8MPa under the conditions of a fluidized solidified soil moisture content of 35-55% and a curing agent dosage of 5-20%, it does not pay attention to the loss of fluidity after standing for more than 1h. From the perspective of strength development, a high strength value can be reached in 6 hours, indicating that a violent hydration reaction occurred in the early stage to form strength. It can be predicted that the fluidity will be significantly reduced after standing for more than 1 hour, which is difficult to meet the requirements of the actual engineering of premixed fluidized solidified soil with a long transportation distance. In addition, the patented technology mainly uses cement as a curing agent. Although the unconfined compressive strength data under high water content conditions (such as water content greater than 100%) is not given, a large number of studies have shown that cement has limited curing effect on high water content mud.
[0015] In summary, it is difficult to achieve a balanced unity between early strengthening and premixing of fluidized solidified soil with existing technologies, and new technical means need to be developed to prepare premixed early-strength fluidized solidified soil. Summary of the invention
[0016] Purpose of the invention: The first purpose of the present invention is to provide a premixed early-strength fluidized solidified soil that achieves a balanced balance between early strengthening and premixing of fluidized solidified soil; the second purpose of the present invention is to provide a method for preparing the premixed early-strength fluidized solidified soil.
[0017] Technical solution: The premixed early-strength fluidized solidifying soil described in the present invention comprises the following components, by weight: 85-96 parts of mud, 4-15 parts of curing agent, 0.008-0.05 parts of retarder, 0.0048-0.03 parts of slow-absorbing water microspheres, and 0.012-0.06 parts of slow-release early-strength particles; wherein the slow-absorbing water microspheres comprise an inner core and an outer shell, the inner core is a water-absorbing material, and the outer shell is a composite of acrylic resin No. II (Eudragit Ll00 type) and No. III (Eudragit Sl00 type); the slow-release early-strength particles comprise an inner core and an outer shell, the inner core is an early-strength agent, and the outer shell is acrylic resin No. III (Eudragit Sl00 type).
[0018] Preferably, when the shell of the slow-absorbing microbeads is granulated, the wall thickness of the composite slurry of acrylic resin No. II and No. III is 150-200 μm.
[0019] Preferably, when the shell of the sustained-release early-strength granules is granulated, the wall thickness of the acrylic resin No. III slurry is 180-220 μm.
[0020] Preferably, the mass ratio of acrylic resin No. II to No. III in the shell material of the slow-absorbing water microbeads is 1:1 to 1:2.
[0021] The slow-absorbing microbeads use acrylic resins II and III as shell materials to wrap the absorbent material. During transportation, the absorbent material does not absorb water because it is wrapped by the shell, so that the fluidized solidified soil has good fluidity. The shell material gradually dissolves during transportation. After construction, the inner core absorbent material is released, and the super absorbent resin gradually absorbs water, consumes a large amount of free water in the fluidized soil, increases the ion solubility in the pore solution of the fluidized soil, accelerates the hydration reaction process, and improves the strength of the fluidized solidified soil; at the same time, the ultra-early strength cementitious material composed of sulfoaluminate cement, ordinary silicate cement, and calcium formate in the slow-absorbing microbeads rapidly undergoes a hydration reaction after encountering water to generate a cementitious product, which fills the pores between the super absorbent resin particles and cements the super absorbent resin particles, so that the super absorbent resin after water absorption and expansion has a stable volume and strength.
[0022] Preferably, the water-absorbing microbeads include a water-absorbing material in the inner core including: 85-90% super absorbent resin, 6-10% sulphoaluminate cement, 3.85-4.95% P.O42.5 ordinary Portland cement, and 0.05-0.15% calcium formate.
[0023] Preferably, the particle size of the super absorbent resin is 100-150 meshes, the water absorption multiple of pure water is ≥100 times, and the water absorption multiple of mud solution is ≥35 times.
[0024] Generally, the strength of water-absorbing materials such as super absorbent resins is very low after absorbing water, which will cause stress concentration and damage to the soil around the super absorbent resin when the fluidized solidified soil is subjected to external loads, thereby reducing the strength of the fluidized solidified soil. The present invention rapidly forms a bond with the super absorbent resin after absorbing water by adding a super early strength component composed of sulphoaluminate cement, ordinary silicate cement and calcium formate to the slow-absorbing microbeads, thereby improving the strength of the super absorbent resin, effectively making up for the deficiency of the low strength of the super absorbent resin, and improving the strength of the fluidized solidified soil.
[0025] The slow-release early-strength particles wrap the early-strength agent through the acrylic resin No. III shell, preventing the early-strength component from participating in the reaction in the early stage of the preparation of the fluidized solidified soil, thereby realizing the premixed slow-setting function. During transportation, the shell gradually dissolves, and the calcium formate and calcium nitrite in the slow-release early-strength particles dissolve in the pore solution of the fluidized soil to play an early-strength role, so that the fluidized solidified soil quickly forms strength.
[0026] Preferably, the early strength agent is a compound of calcium formate and calcium nitrite; further preferably, the mass ratio of calcium formate to calcium nitrite is 1:1 to (2:1).
[0027] Preferably, the retarder is compounded by citric acid and plant protein in a mass ratio of (6:4) to (3:7).
[0028] Preferably, the curing agent is composed of the following raw materials in percentage by mass: 55-75% mineral powder, 6-15% cement, 3-5% lime, 2-6% red mud, 4-6% steel slag, and 8-12% gypsum.
[0029] Preferably, the mineral powder is S95 mineral powder with a specific surface area of 550-600m 2 / kg.
[0030] Preferably, the cement is P.O42.5 type silicate cement
[0031] Preferably, the lime is quicklime with an effective calcium oxide content greater than 75%.
[0032] Preferably, the red mud has a particle size of 0.1 to 0.2 mm, a silicon dioxide and aluminum oxide content of not less than 50%, and a pH value of ≥11.
[0033] Preferably, the gypsum is hemihydrate gypsum with a calcium sulfate content greater than 80%.
[0034] Preferably, the mud is silt that has not been dehydrated by filtration or flocculation, bored pile mud or mud prepared from engineering debris, the initial moisture content of the mud is 80% to 160%, the initial fluidity of the mud is not less than 220 mm, and the maximum particle size is not greater than 20 mm.
[0035] The method for preparing the premixed early-strength fluidized solidified soil of the present invention is characterized by comprising the following steps:
[0036] (1) preparing mud;
[0037] (2) weighing the curing agent raw materials and mixing them evenly to obtain a curing agent;
[0038] (3) mixing the curing agent and water evenly, adding a retarder and mixing evenly to obtain a curing agent slurry;
[0039] (4) Add the curing agent slurry, slow water absorption micro beads, and slow-release early strength particles to the mud prepared in step (1), mix them evenly, and transport them to the construction site by tank truck for construction.
[0040] Preferably, the preparation method of the slow water-absorbing microbeads is:
[0041] (1) adding the core raw material into a granulator to obtain a mixed material with a diameter of 1.0 to 2.0 mm;
[0042] (2) The mixed material prepared in step (1) is loaded into a multifunctional granulating coating machine, and a slurry formed by a composite of acrylic resins No. II and No. III is sprayed to obtain slow-absorbing water microbeads.
[0043] The preferred method for preparing the sustained-release early-strength granules is:
[0044] (1) adding the core raw material into a granulator to obtain a mixed material with a diameter of 0.5 to 1.0 mm;
[0045] (2) The mixed material prepared in step (1) is loaded into a multifunctional granulating coating machine, and the acrylic resin No. III slurry is sprayed to obtain slow-release early-strength granules.
[0046] Invention mechanism: The curing agent, retarder and water are mixed in proportion to prepare a curing agent slurry. At this time, the citric acid in the retarder dissociates into H + and acid ions, which react with Ca in cement, lime and gypsum 2+ Mg 2+ 、Al 3+ The cations form unstable complex precipitation, forming a thick and amorphous complex film on the surface of cement and lime particles, which controls the Ca in the liquid phase at the initial stage of hydration. 2+ Mg 2+ 、Al 3+concentration, thereby slowing down the hydration rate. Plant protein reacts with Ca on the surface of gypsum 2+ Ions combine and cover the surface of the crystal nucleus of gypsum, reducing the surface energy of the crystal nucleus and inhibiting the growth of the crystal nucleus. Therefore, when the curing agent slurry is mixed with the mud, due to the retarding effect of the retarder, the amount of gelling product generated in the early 1 to 2 hours of the preparation of the fluidized solidified soil is very small, and the fluidity loss of the fluidized solidified soil is not obvious.
[0047] After the curing agent slurry, slow-absorbing water beads, slow-release early-strength particles and mud are mixed, they are transported to the construction site by tank trucks for construction.
[0048] During transportation, the amorphous complex film layer on the surface of cement and lime particles gradually decomposes, and hydration will continue normally to form cementitious products and cemented soil particles. In the alkaline environment provided by cement, lime, red mud, and steel slag, on the one hand, the glass in the mineral powder and steel slag disintegrates and reacts with gypsum to form cementitious products such as CSH gel and calcium aluminate, which fill the pores and cement the soil particles while converting part of the free water in the fluidized solidified soil into mineral bound water, thereby improving the strength and density of the fluidized solidified soil; while cement and lime are hydrated, they also promote the hydration reaction of red mud to form cementitious substances, which further fill the internal pores of the fluidized solidified soil and cement the soil particles while consuming free water, thereby improving the strength of the fluidized solidified soil. On the other hand, in an alkaline environment, the shell of the slow-absorbing microbeads, which is composed of acrylic resin No. II (Eudragit Ll00) and No. III (Eudragit Sl00), is gradually dissolved in the pore solution of the fluidized solidified soil. After construction, the inner core water-absorbing material is released, and the super absorbent resin gradually absorbs water, consumes a large amount of free water in the fluidized soil, increases the ion solubility in the pore solution of the fluidized soil, accelerates the hydration reaction process, and improves the strength of the fluidized solidified soil; at the same time, the ultra-early strength cementitious material composed of sulfoaluminate cement, ordinary silicate cement, and calcium formate in the slow-absorbing microbeads rapidly undergoes a hydration reaction when it meets water to generate a cementitious product, which fills the pores between the super absorbent resin particles and cements the super absorbent resin particles, so that the super absorbent resin after water absorption and expansion has a stable volume and strength.
[0049] Although the slow-release early-strength particles contain two early-strength components, calcium formate and calcium nitrite, the acrylic resin No. III slurry wrapped in the shell of the slow-release early-strength particles prevents the early-strength components from participating in the reaction in the early stage of the preparation of fluidized solidified soil, thereby realizing the premixed slow-setting function. The shell of acrylic resin No. III (Eudragit Sl00) on the surface of the slow-release early-strength particles will also gradually dissolve in the alkaline environment provided by cement, lime, red mud and steel slag. However, since the dissolution pH value of acrylic resin No. III (Eudragit Sl00) is higher than that of acrylic resin No. II (Eudragit Ll00), and the slurry shell on the surface of the slow-release early-strength particles is slightly thicker than the slurry shell on the surface of the slow-absorbing microspheres, when the highly absorbent resin in the slow-absorbing microspheres is saturated with water, the shell of acrylic resin No. III (Eudragit Sl00) on the surface of the slow-release early-strength particles dissolves, and the calcium formate and calcium nitrite in the slow-release early-strength particles dissolve in the pore solution of the fluidized soil to play an early-strengthening role, so that the fluidized solidified soil quickly forms strength and realizes the early-strength function.
[0050] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) In the premixed early-strength fluidized solidified soil, by adopting slow-absorbing microspheres and slow-release early-strength particles, a balance between early strengthening and premixing of the fluidized solidified soil is achieved; (2) The premixed early-strength fluidized solidified soil can directly perform fluidized solidification treatment on high-water content mud (water content above 80%), the fluidity of the newly mixed fluidized solidified soil is above 220 mm, and the fluidity after standing for 2 hours is above 200 mm, the 24h strength can reach 0.2-0.6 MPa, and the 28d strength can reach 0.8-3.5 MPa, which meets the current municipal and road engineering requirements for premixed fluidized soil backfill and high early strength; (3) The preparation method of the premixed early-strength fluidized solidified soil is simple and easy to industrialize. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below in conjunction with embodiments.
[0052] Example 1
[0053] The premixed early-strength fluidized solidified soil of the present invention comprises the following components, by weight: 95 parts of mud, 4.969 parts of curing agent, 0.01 parts of retarder, 0.006 parts of slow-absorbing water microspheres, and 0.015 parts of slow-release early-strength particles.
[0054] The curing agent package includes the following components by mass percentage: 70% mineral powder, 12% P.O42.5 ordinary Portland cement, 3% lime, 3% red mud, 2% steel slag, and 10% gypsum; the mineral powder is S95 mineral powder with a specific surface area of 560m 2 / kg; the cement is P.O42.5 type silicate cement; the lime is quicklime with an effective calcium oxide content of 76.6%; the average particle size of the red mud is 0.12mm, the content of silicon dioxide and aluminum oxide is 58.1%, and the pH value is 11.3; the steel slag is mainly composed of calcium oxide 45.1%, silicon dioxide 11.3%, magnesium oxide 11.1%, aluminum oxide 9.8%, and a specific surface area of 580m 2 / kg; the gypsum is hemihydrate gypsum with a calcium sulfate content of 83.2%.
[0055] The retarder is compounded by citric acid and vegetable protein in a mass ratio of 6:4.
[0056] The core material of the slow-absorbing water microspheres comprises, by mass fraction, 85% of super absorbent resin, 10% of sulphoaluminate cement, 4.9% of P.O42.5 ordinary Portland cement, and 0.1% of calcium formate; wherein the super absorbent resin has a particle size of 100 to 150 meshes, a water absorption multiple of ≥100 times for pure water, and a water absorption multiple of ≥35 times for mud solution; and the preparation method comprises the following steps:
[0057] (1) adding the core raw material into a granulator and stirring for 3 min at a stirring rate of 500 to 600 r / min to obtain a mixture with a diameter of 1.0 to 2.0 mm;
[0058] (2) The mixed material prepared in step (1) is loaded into a multifunctional granulating coating machine, and a slurry composed of acrylic resin No. II and No. III is sprayed, and the slurry wall thickness is 150 to 200 μm to obtain slow water-absorbing microbeads; the mass ratio of the sprayed acrylic resin No. II and No. III is 1:1.
[0059] The slow-release early-strengthening granules have an early-strengthening agent in the inner core of calcium formate and calcium nitrite in a mass ratio of 2:1, and a preparation method thereof comprises the following steps:
[0060] (1) Weigh the raw materials according to the mass ratio of calcium formate to calcium nitrite of 2:1;
[0061] (2) adding the calcium formate and calcium nitrite into a granulator, stirring for 3 minutes at a stirring rate of 500 to 600 r / min to obtain a mixture with a diameter of 0.5 to 1.0 mm;
[0062] (3) The mixture obtained in step (2) is loaded into a multifunctional granulating coating machine, and is sprayed with acrylic resin No. III (Eudragit S100 type) slurry with a slurry wall thickness of 180 to 220 μm to obtain sustained-release early-strength granules.
[0063] The preparation method of the premixed early-strength fluidized solidified soil comprises the following steps:
[0064] (1) The mud was prepared using river silt, with an initial water content of 83.2%, an initial fluidity of 265 mm, and a maximum particle size of 20 mm;
[0065] (2) weighing the curing agent raw materials according to the above proportions, stirring them by mechanical stirring for 3 to 4 minutes at a stirring rate of 30 to 60 r / min to prepare the curing agent;
[0066] (3) Stir the curing agent and water in a mass ratio of 1:1, add a retarder in proportion, and continue stirring for 1 to 2 minutes to prepare a curing agent slurry;
[0067] (4) Add the curing agent slurry, slow water absorption micro beads, and slow-release early strength particles according to the above ratio into the mud prepared in (1), and use mechanical stirring at a stirring rate of 30 to 60 r / min and a stirring time of 1 to 2 min to obtain a flow solidification diagram.
[0068] Example 2
[0069] The premixed early-strength fluidized solidified soil of the present invention comprises the following components by weight: 90 parts of mud, 9.925 parts of a curing agent, 0.025 parts of a retarder, 0.02 parts of slow-absorbing water microspheres, and 0.03 parts of slow-release early-strength particles.
[0070] The remaining conditions are the same as in Example 1.
[0071] Example 3
[0072] The premixed early-strength fluidized solidified soil of the present invention comprises the following components by weight: 85 parts of mud, 14.88 parts of curing agent, 0.05 parts of retarder, 0.025 parts of slow-absorbing water microspheres, and 0.045 parts of slow-release early-strength particles.
[0073] The remaining conditions are the same as in Example 1.
[0074] Example 4
[0075] The premixed early-strength fluidized solidifying soil of the present invention comprises the following components by weight: 90 parts of mud, 9.885 parts of curing agent, 0.035 parts of retarder, 0.03 parts of slow-absorbing water microbeads, and 0.05 parts of slow-release early-strength particles; the mud is bored pile mud with a water content of 130.5%.
[0076] The inner core material of the slow-absorbing water microspheres comprises, by mass fraction, 90% of super absorbent resin, 6% of sulphoaluminate cement, 3.9% of P.O42.5 ordinary Portland cement, and 0.1% of calcium formate.
[0077] The remaining conditions are the same as in Example 1.
[0078] Example 5
[0079] The premixed early-strength fluidized solidifying soil of the present invention comprises the following components by weight: 90 parts of mud, 9.902 parts of curing agent, 0.008 parts of retarder, 0.03 parts of slow-absorbing water microbeads, and 0.06 parts of slow-release early-strength particles; the mud is bored pile mud with a water content of 155%.
[0080] The inner core material of the slow-absorbing water microspheres comprises, by mass fraction, 90% of highly absorbent resin, 6% of sulphoaluminate cement, 3.85% of P.O42.5 ordinary Portland cement, and 0.15% of calcium formate.
[0081] The remaining conditions are the same as in Example 1.
[0082] Comparative Example 1
[0083] The same as Example 2, except that the curing agent is changed to 100% P.O42.5 ordinary Portland cement.
[0084] Comparative Example 2
[0085] The same as Example 2, except that no retarder was added.
[0086] Comparative Example 3
[0087] The same as Example 2, except that the slow-absorbing water microbeads are not incorporated.
[0088] Comparative Example 4
[0089] The same as Example 2, except that the slow-release early-strengthening particles are not incorporated.
[0090] Comparative Example 5
[0091] The method is the same as Example 2, except that the fluidized solidified soil is prepared by the following steps: the raw materials of the curing agent are weighed in proportion, and the curing agent is obtained after being mixed evenly; the curing agent, retarder, slow-absorbing water microbeads, and slow-release early-strength particles are added to the mud according to the designed mix ratio, and mechanical stirring is adopted with a stirring rate of 30 to 60 r / min and a stirring time of 1 to 2 min to obtain the fluidized solidified soil.
[0092] Comparative Example 6
[0093] The same as Example 2, except that the core component of the slow-absorbing water microbeads is composed of the following mass percentages: 100% super absorbent resin.
[0094] Comparative Example 7
[0095] The same as Example 2, except that the surface of the slow-absorbing microbeads is not sprayed with the slurry formed by the composite of acrylic resin No. II (Eudragit L100) and No. III (Eudragit S100).
[0096] Comparative Example 8
[0097] The same as Example 2, except that the fluidized solidified soil is prepared by the following steps: the raw materials of the inner core of the slow-absorbing water microbeads are weighed in proportion, mixed evenly, and loaded into a multifunctional granulating coating machine, and a slurry prepared by compounding acrylic resin No. II (Eudragit Ll00 type) and No. III (Eudragit Sl00 type) in a mass ratio of 1:1 is sprayed, and the slurry wall thickness is 150-200 μm, to obtain slow-absorbing water microbeads; the raw materials of the slow-release early-strength granules are weighed in proportion, mixed evenly, and loaded into a multifunctional granulating coating machine, and a slurry prepared by compounding acrylic resin No. II (Eudragit Ll00 type) and No. III (Eudragit Sl00 type) in a mass ratio of 1:1 is sprayed, and the slurry wall thickness is 150-200 μm, to obtain slow-release early-strength granules. Weigh the raw materials of the curing agent in proportion, mix them evenly to obtain the curing agent; weigh the curing agent in proportion, mix the curing agent and water in a ratio of 1:1 evenly, add the retarder in proportion and continue stirring for 1 to 2 minutes to prepare the curing agent slurry; add the curing agent slurry, slow-absorbing water microbeads, and slow-release early-strength particles into the mud according to the designed mix ratio, and use mechanical stirring at a stirring rate of 30 to 60 r / min and a stirring time of 1 to 2 minutes to obtain fluidized solidified soil.
[0098] Performance Testing
[0099] The compressive strength and fluidity of the embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0100] Test method: The unconfined compressive strength of the prepared fluidized solidified soil is tested according to the method specified in JGJ / T 233 "Cement-Soil Mix Design Code"; the fluidity of the prepared fluidized solidified soil is tested according to the test method specified in T / CECS1175-2022 "Technical Standard for Self-Compacting Solidified Soil Filling".
[0101] Table 1 Test results of embodiments and comparative examples
[0102]
[0103] From the data in Table 1, it can be seen that the fluidized soil prepared by the five mix ratios given in Examples 1 to 5 all have high initial fluidity, and the fluidity is greater than 200 mm after standing for 2 hours, which meets the requirement of T / CECS1175-2022 "Technical Standard for Self-compacting Solidified Soil Filling" that the fluidity of pumped fluidized solidified soil is not less than 160 mm, and the 24h unconfined compressive strength is greater than 0.21 MPa, and the 28d unconfined compressive strength is more than 0.93 MPa, and the highest can reach 3.5 MPa. Therefore, the premixed early-strength fluidized solidified soil material disclosed in the present invention fully meets the current municipal and road engineering requirements for premixed and high early strength of fluidized soil backfill, and achieves a balanced unity between early strengthening and premixing of fluidized solidified soil, which has important reference significance for promoting the application of fluidized solidified soil in municipal and road engineering.
[0104] By comparing Examples 1 to 5 with Comparative Example 1, it is found that when the curing agent disclosed in the present invention is not used and 100% ordinary Portland cement is used, the 24h strength is only 0.03MPa, the 7d unconfined compressive strength is only 0.22MPa, and the 28d unconfined compressive strength is only 0.45MPa. Although the 28d unconfined compressive strength meets the minimum backfill strength requirements of fertilizer troughs, cavities, etc., it does not have the early strength function.
[0105] Comparing Example 2 and Comparative Example 2, when no retarder is added, due to the early hydration of the components of the curing agent, the fluidity loss of Comparative Example 2 is significantly faster than that of Example 2, and the fluidity of Comparative Example 2 is only 146 mm after standing for 1 hour, which is difficult to meet the requirements of premixing.
[0106] Combining Example 2 with Comparative Examples 3 and 4, it can be obtained that the slow-absorbing water microspheres and the slow-release early-strength particles have little effect on the initial fluidity, 1h fluidity and 2h fluidity of the fluidized solidified soil, but the early-strength effect produced by the simultaneous use of the slow-absorbing water microspheres and the slow-release early-strength particles is better than the sum of the lifting effects produced by the slow-absorbing water microspheres and the slow-release early-strength particles alone, indicating that there is functional mutual support between the technical solution of the slow-absorbing water microspheres and the technical solution of the slow-release early-strength particles provided by the present invention.
[0107] Comparing Example 2 and Comparative Example 5, when the curing agent, retarder, slow water absorption micro beads, and slow-release early strength particles are directly added to the mud (the curing agent, water, and retarder are not mixed in advance to prepare the curing agent slurry), due to the water absorption effect of each component of the curing agent, the initial fluidity of Comparative Example 5 is significantly lower than that of Example 2. In addition, since the retarder is directly added to the mud, the retarder component is adsorbed on the surface of the soil particles, which weakens the retarding effect of the retarder on the curing agent. The fluidity of Comparative Example 5 after standing for 2 hours is only 108mm, which is difficult to meet the pumping requirements.
[0108] By comparing Example 2 and Comparative Example 6, it can be found that the super early strength component composed of sulphoaluminate cement, ordinary Portland cement and calcium formate in the slow-absorbing water microspheres plays an important role in the strength of the microspheres after absorbing water. When the super early strength component composed of sulphoaluminate cement, ordinary Portland cement and calcium formate is missing, the strength of the super absorbent resin after water absorption and expansion is poor, which makes the fluidized solidified soil easily damaged at the location of the super absorbent resin after being compressed, thereby reducing the strength of the fluidized solidified soil.
[0109] By comparing Example 2 with Comparative Example 7, it is found that when the step of spraying the slurry composed of acrylic resin No. II (Eudragit L100) and No. III (Eudragit S100) on the surface of the slow-absorbing microspheres is omitted, the effects of the slow-absorbing microspheres on the fluidity and unconfined compressive strength are not as good as those in Example 2. This is mainly because when the surface of the slow-absorbing water beads lacks the shell composed of acrylic resin No. II (Eudragit Ll00) and No. III (Eudragit Sl00), the slow-absorbing water beads will absorb a large amount of free water during the preparation of the slurry by the curing agent and the mixing of the fluidized solidified soil, resulting in a decrease in fluidity; and when the slow-absorbing water beads lack the protection of the shell composed of acrylic resin No. II (Eudragit Ll00) and No. III (Eudragit Sl00), it is difficult to maintain the integrity of the slow-absorbing water beads, and they are easily dispersed in the fluidized solidified soil. The ultra-early strength components composed of sulfoaluminate cement, ordinary silicate cement and calcium formate in the slow-absorbing water beads are difficult to effectively bond and solidify the highly absorbent resin after water absorption, which significantly reduces the strength of the fluidized solidified soil.
[0110] By comparing Example 2 with Comparative Example 8, it is found that when the surface of the slow-absorbing water microspheres and the slow-release early-strength particles adopt the same shell material and thickness, although the fluidity and the 7d and 28d unconfined compressive strength are not much different from those of Example 2, the 24h unconfined compressive strength in Comparative Example 8 is significantly lower than that of Example 2. This is mainly because when the surface of the slow-absorbing water microspheres and the slow-release early-strength particles adopt the same shell material and thickness, the dissolution time of the shell on the surface of the slow-absorbing water microspheres and the slow-release early-strength particles is basically the same, and the water absorption and dissolution of the early-strength component of the super absorbent resin occur simultaneously. At this time, the super absorbent resin will absorb part of the early-strength component, reduce the solubility of the early-strength component, and weaken the early-strength effect. In Example 2, the shell of the slow-absorbing water microspheres is designed to dissolve first, and the super absorbent resin in the slow-absorbing water microspheres absorbs water and expands, reducing the free water content in the fluidized solidified soil, and the super early-strength component composed of sulphoaluminate cement, ordinary silicate cement, and calcium formate in the water-absorbing microspheres is rapidly hydrated to fill the pores of the super absorbent resin and form strength, thereby ensuring the stability of the slow-absorbing water microspheres. When the shell of the slow-release early-strength particle dissolves, the early-strength component dissolves in the remaining free water in the fluidized solidified soil, which can form a higher solubility, quickly promote the hydration of the curing agent, and form early strength. Therefore, the "gradient" dissolution technology of the slow-absorbing water microspheres and the shell of the slow-release early-strength particle provided in the present invention plays an important role in ensuring the 24h unconfined compressive strength.
Claims
1. A premixed early-strength fluidized solidified soil, It is characterized in that The raw materials include the following components by weight: 85-96 parts of mud, 4-15 parts of curing agent, 0.008-0.05 parts of retarder, 0.0048-0.03 parts of slow-absorbing water micro beads, and 0.012-0.06 parts of slow-release early-strength particles; The slow-absorbing water microbeads include a core and an outer shell, wherein the core is a water-absorbing material and the outer shell is a composite of acrylic resins No. II and No. III; The slow-release early-strengthening granules comprise a core and an outer shell, wherein the core is an early-strengthening agent and the outer shell is acrylic resin No. III.
2. The premixed early-strength fluidized solidified soil according to claim 1, It is characterized in that When the shell of the slow-absorbing microbeads is granulated, the wall thickness of the composite slurry of acrylic resin No. II and No. III is 150-200 μm.
3. The premixed early-strength fluidized solidified soil according to claim 1, It is characterized in that When the shell of the slow-release early-strength granules is granulated, the wall thickness of acrylic resin No. III slurry is 180-220 μm.
4. The premixed early-strength fluidized solidified soil according to claim 1, It is characterized in that The water-absorbing material in the inner core of the slow-absorbing microbeads comprises, by mass fraction, 85-90% of super absorbent resin, 6-10% of sulphoaluminate cement, 3.85-4.95% of P.O42.5 ordinary Portland cement, and 0.05-0.15% of calcium formate.
5. The premixed early-strength fluidized solidified soil according to claim 4, It is characterized in that The particle size of the highly absorbent resin is 100-150 meshes, the water absorption multiple of pure water is ≥100 times, and the water absorption multiple of mud solution is ≥35 times.
6. The premixed early-strength fluidized solidified soil according to claim 1, It is characterized in that The retarder is compounded by citric acid and vegetable protein in a mass ratio of (6:4) to (3:7).
7. The premixed early-strength fluidized solidified soil according to claim 1, It is characterized in that The mud is silt that has not been filtered or flocculated and dehydrated, bored pile mud or mud prepared from engineering debris, the initial water content of the mud is 80% to 160%, the initial fluidity of the mud is not less than 220mm, and the maximum particle size is not greater than 20mm.
8. A method for preparing the premixed early-strength fluidized solidified soil according to any one of claims 1 to 7, It is characterized in that The following steps are involved: (1) preparing mud; (2) weighing the curing agent raw materials and mixing them evenly to obtain a curing agent; (3) mixing the curing agent and water evenly, adding a retarder and mixing evenly to obtain a curing agent slurry; (4) Add the curing agent slurry, slow water absorption micro beads, and slow-release early strength particles to the mud prepared in step (1), mix them evenly, and transport them to the construction site by tank truck for construction.
9. The method for preparing the premixed early-strength fluidized solidified soil according to claim 8, It is characterized in that The preparation method of the slow water-absorbing microbeads is as follows: (1) adding the core raw material into a granulator and stirring to obtain a mixed material with a diameter of 1.0 to 2.0 mm; (2) The mixed material prepared in step (1) is loaded into a multifunctional granulating coating machine, and a slurry formed by a composite of acrylic resins No. II and No. III is sprayed to obtain slow-absorbing water microbeads.
10. The method for preparing the premixed early-strength fluidized solidified soil according to claim 8, It is characterized in that The preparation method of the sustained-release early-strength granules is as follows: (1) adding the core raw material into a granulator to obtain a mixed material with a diameter of 0.5 to 1.0 mm; (2) The mixed material prepared in step (1) is loaded into a multifunctional granulating coating machine, and the acrylic resin No. III slurry is sprayed to obtain slow-release early-strength granules.
